Exploring health professionals' views regarding the optimum physical environment for palliative and end of life care in the acute hospital setting: a qualitative study. Issue 2 (9th August 2011) - Gardiner, Clare; Brereton, Louise; Gott, Merryn; Ingleton, Christine; Barnes, Sarah
Abstract : Background: Limited evidence exists relating to key elements of the optimum physical hospital environment for patients receiving palliative and end of life care in acute hospitals. The aim of this study was to explore the perspectives of health professionals regarding the optimum physical environment for palliative and end of life care in the acute hospital setting. Methods: Qualitative focus group study with 24 health professionals from an acute hospital, a community hospital and a hospice. Findings Participants agreed that provision of appropriate privacy options was key to achieving an optimum physical environment. However, there was little consensus as to whether single room accommodation or multi-bed accommodation was the most appropriate. A comfortable and homely environment is important, but difficult to achieve in a clinically focused environment. The hospital environment may also be suboptimal for staff provision of care. The environmental needs of families should be considered alongside the needs of patients. Conclusion: Many deficiencies exist in physical hospital environments for patients at the end of life. However, changes to the hospital environment are limited by resource restrictions, increasing rules and regulations, and a focus on clinical aspects of care. Further research is needed to establish patient and family views about the optimum physical hospital environment, to explore ways in which an appropriate environment can be most effectively achieved and to ensure engagement with planners, designers and stakeholders when commissioning new hospitals or renovating existing facilities.